Caring in crisis: addressing patient safety, burnout, and long hours in healthcare - Shaheen, Fabeeha; Shaheen, Qareena (Journal of the Pakistan Medical Association, 2024)
Madam, The World Health Organization defines patient safety as preventing errors and adverse effects to patients associated with health care and “to do no harm to patients”. Specifically, in low and middle-income countries (LMICs), about 134 million adverse events occur each year due to unsafe care in hospitals, resulting in 2.6 million deaths annually. [1] Along with other determining factors, professional well-being, long hours, and burnout syndromes also influence patient care. [2] Burnout is a condition directly linked to workplace environment, stemming from occupational stress and extended working hours. Garcia, C.L. et al., through meta-analysis, found a relationship between the development of burnout and patient safety actions, with a probability of superiority of 66.4%. High levels of burnout and worsening patient safety are related to external factors such as high workload, long working hours, lack of a secure environment, and interpersonal relationships. [3] These findings raise concerns, particularly in a country like Pakistan, where the extent of understaffing and high workload can be inferred from the following statistics: The doctor-to-population ratio in Pakistan was 1:1000 in 2018 [4]. In contrast, the doctor-to-population ratio in Malaysia was 2.2:1000 in 2018 [5]. As a result of this shortage, the current workforce in Pakistan is negatively affected. In a study by Kasi PM et al. on postgraduate trainees in Pakistan, individuals under stress were more likely to report longer working hours. This increased workload made them prone to medical errors, which ultimately undermines the patient safety culture. A study conducted at a tertiary care hospital in Pakistan using the Hospital Survey on Patient Safety Culture (HSOPSC) compared the benchmarks from hospitals in the USA and discovered that high staff workload is a significant concern among staff [6] In Pakistan, where healthcare resources are limited, fostering a culture of effective work-hour management and breaks is essential for creating a healthier and safer environment for health professionals and patients. Ensuring adequate staffing levels to distribute the workload and prevent overburdening is essential. Providing designated areas for relaxation, offering mental health resources and mindfulness programmes like yoga or meditation can help doctors to cope with stress. Furthermore, promoting a culture of multidisciplinary teamwork, a mentorship program, and effective handover protocols during shift changes can ensure continuity of care. Medical institutes should invest in technology that can streamline administrative tasks and reduce paperwork burden. ---Continue